Business Owner Commitment Mediates the Relationship Between Leadership and MSME Performance - Adam, Duki; Banani, Ade; Purnomo, Ratno (Journal of Posthumanism, 2025)
In the midst of business dynamics, leaders who integrate these values tend to create a positive work environment, enhance business owner commitment, and drive better performance in MSMEs. This study aims to analyze the impact of value-based leadership on business owner commitment and MSME performance in Purwakarta Regency. The study identifies the extent to which the integration of ethical and moral values in leadership style can enhance the dedication, loyalty, and motivation of business owners. The research population consists of 6,324 MSMEs, with a sample size of 221 MSME owners in Purwakarta Regency, West Java, determined using Slovin’s formula with a 5% margin of error. The analysis was conducted using SmartPLS. The results indicate that value-based leadership does not affect MSME performance but does influence business owner commitment, which in turn affects MSME performance.